Удосконалений методичний підхід до визначення економічно доцільного потенціалу енергозбереження в енергоємних видах економічної діяльності - Maliarenko O.Ye.; Maistrenko N.Yu.; Stanytsina V.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2015)
It was improved the technique for determining the economically appropriate energy saving potential due to changes in the registering the statistical reporting (introduction of KVED-2010 to replace KVED-2005) and in law (adoption of Tax Code), which led to an adjustment in comprehensive methodology for assessment of energy efficiency of saving measures. For the production levels the selected criteria are maximum reduction in energy output or increase of the process efficiency, reduction specific emissions, discharges and waste disposal (as a result of energy efficiency measures), positive economic effect, which is obtained in implementation of energy saving measures for a year. The criteria for assessment of efficiency of energy-saving measures at the level of section and enlarged sections (sectors) are maximum decrease in energy intensity of gross value added or output, reduction of environmental tax at the level of economic activity, positive economic effect, which is obtained in implementation of energy-saving measures by economic activity. At the country level the criteria are determined by the total savings obtained in implementing measures in sections by economic activity and intersectional energy-saving measures, maximum reduction in energy intensity of GDP or output, reduction in environmental tax in the country, positive economic effect, which is obtained in implementation of energy-saving measures in all types of economic activity. On the base of advanced technique it was defined the cost-effective energy-saving potential in production of cast-iron, coke and cement until 2030, which estimated value, respectively, is 1126 ths. tonnes of equivalent fuel, 843 ths. tonnes of equivalent fuel, and 770 ths. tonnes of equivalent fuel. The total energy-saving potential of discussed manufactures will be 2740 ths. tonnes of equivalent fuel, or 11.2% of final fuel consumption by processing industry, or 10.4% of the final fuel consumption by "Industry" sector, and almost 5% of the final fuel consumption by countries regarding the level of 2013. At an average cost of equivalent fuel during 2013 – 2551.9 UAH/ton of equivalent fuel, in these industries the total cost of saved energy resources will reach 7 billion at prices of 2013.